Course Certificate Integration Based on Wireless Communication '1+X' Intelligent Finance and Taxation. (8th April 2022) - Li, Jing
Abstract : Due to the ever-changing market environment and fierce competition, tax personnel are increasingly pursuing intelligence. Based on the background of smart finance and taxation, this article explains the issues related to the "1 + X " certificate and analyzes the development ideas and reform directions of the teaching plan and certificate integration teaching mode. This paper presents a study on the integration of academic certificates under the background of "1 + X " intelligent finance and taxation wireless communication. From 2018 to 2019, the development trend of smart finance and taxation has been rising. In 2018, the lowest was 11%, and the highest was 25%; in 2019, the lowest was 16%, and the highest was 37%. The lowest growth rate in 2019 was 5%, and the highest was 21%; the results show that although many relevant personnel understand smart finance and taxation, they have not planned how to use smart finance and taxation to improve their professional capabilities. The results show that smart fiscal and taxation is becoming more and more important in social development and has been widely used. However, traditional fiscal and taxation teaching can no longer meet the requirements of today's society for fiscal and taxation personnel, so related fiscal and taxation teaching should be innovated.